Utilization of Ayurveda in Health Care: An Approach for Prevention, Health Promotion, and Treatment of Disease. Part 1-Ayurveda, the Science of Life - HARI SHARMA, H.M. CHANDOLA,GURDIP SINGH, and GOPAL BASISHT (THE JOURNAL OF ALTERNATIVE AND COMPLEMENTARY MEDICINE Volume 13, Number 9, 2007, pp. 1011-1019, 2007)
Ayurveda is a natural health care system that originated in India more than 5000 years ago. Its main objective is to achieve optimal health and well-being through a comprehensive approach that addresses mind, body, behavior, and environment. Ayurveda emphasizes prevention and health promotion, and provides treatment fordisease. It considers the development of consciousness to be essential for optimal health and meditation as the main technique for achieving this. Treatment of disease is highly individualized and depends on the psychophysiologic constitution of the patient. There are different dietary and lifestyle recommendations for each season of the year. Common spices are utilized in treatment, as well as herbs and herbal mixtures, and special preparations known as Rasayanas are used for rejuvenation, promotion of longevity, and slowing of the aging process. A group of purification procedures known as Panchakarma removes toxins from the physiology. Whereas Western allopathic medicine is excellent in handling acute medical crises, Ayurveda demonstrates anability to manage chronic disorders that Western medicine has been unable to. It may be projected from Ayurveda's comprehensive approach, emphasis on prevention, and ability to manage chronic disorders that its widespread use would improve the health status of the world's population.